2000
DOI: 10.1126/science.290.5490.350
|View full text |Cite
|
Sign up to set email alerts
|

Replaying the Game: Hypnagogic Images in Normals and Amnesics

Abstract: Participants playing the computer game Tetris reported intrusive, stereotypical, visual images of the game at sleep onset. Three amnesic patients with extensive bilateral medial temporal lobe damage produced similar hypnagogic reports despite being unable to recall playing the game, suggesting that such imagery may arise without important contribution from the declarative memory system. In addition, control participants reported images from previously played versions of the game, demonstrating that remote memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 20 publications
7
138
2
2
Order By: Relevance
“…During REM sleep, however, high levels of acetylcholine in the hippocampus suppress feedback from hippocampus to the neocortex, whereas lower levels of acetylcholine and norepinephrine in the neocortex could facilitate the spread of activity within neocortical areas without strong hippocampal influence (37). This is supported by behavioral evidence from amnesiacs that activation of this associative network during sleep is independent of the medial temporal lobe structures and may reflect reactivation of remote memories that are less dependent on the hippocampus (38). In this theoretical framework, REM sleep would allow neocortical structures to reorganize associative hierarchies, in which information from the hippocampus would be reinterpreted in relation to previous semantic representations or nodes.…”
Section: Discussionsupporting
confidence: 60%
“…During REM sleep, however, high levels of acetylcholine in the hippocampus suppress feedback from hippocampus to the neocortex, whereas lower levels of acetylcholine and norepinephrine in the neocortex could facilitate the spread of activity within neocortical areas without strong hippocampal influence (37). This is supported by behavioral evidence from amnesiacs that activation of this associative network during sleep is independent of the medial temporal lobe structures and may reflect reactivation of remote memories that are less dependent on the hippocampus (38). In this theoretical framework, REM sleep would allow neocortical structures to reorganize associative hierarchies, in which information from the hippocampus would be reinterpreted in relation to previous semantic representations or nodes.…”
Section: Discussionsupporting
confidence: 60%
“…However, the possibility that these heterogeneities could be linked to the known intra- (14) and interindividual (7,8) local variations in cortical EEG power during sleep and in preceding local brain activities during waking periods (37-39) cannot be ignored. In addition to this challenge, our results reveal that extensive cortical territories remain activated for several minutes after the thalamic deactivation at sleep onset, a situation that may be propitious to the development of hypnagogic experiences so common during the wake-sleep transition (40,41). In addition, the errors in self-reported sleep latency which commonly is overestimated by several minutes with respect to the objective (polysomnographic) sleep onset (42,43), might result from these persistent and topographically heterogeneous cortical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive training studies have also shown benefits on visuospatial tasks following repeated practice on Tetris, with improvements observed in spatial ability (Okagaki & Frensch, 1994; Terlecki, Newcombe, & Little, 2008), mental rotation (De Lisi & Wolford, 2002; Moreau, 2013) and selective visual attention (Belchior et al, 2013; Green & Bavelier, 2003). Tetris game play can also lead to hypnagogic visual hallucinations that mix Tetris‐shape representations with other memories — the so call ‘Tetris effect’ (Kusse, Shaffii‐LE Bourdiec, Schrouff, Matarazzo, & Maquet, 2012; Stickgold, 2000). …”
mentioning
confidence: 99%